2022
DOI: 10.3390/separations9090262
|View full text |Cite
|
Sign up to set email alerts
|

Multiprotein Inhibitory Effect of Dietary Polyphenol Rutin from Whole Green Jackfruit Flour Targeting Different Stages of Diabetes Mellitus: Defining a Bio-Computational Stratagem

Abstract: The anti-diabetic potential of whole unripe jackfruit (peel with pulp, flake, and seed) was investigated using inhibitory assays for α-glucosidase, α-amylase, aldose reductase, and glycation at multiple stages. Using activity-guided repeated fractionation on a silica gel column chromatography, dietary flavonoid rutin with potent antihyperglycemic activity was extracted from the methanol extract of whole jackfruit flour (MJ). Rutin was found to inhibit both α-glucosidase (IC50: 7.86 µg/mL) and α-amylase (IC50: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 68 publications
7
13
0
Order By: Relevance
“…The usage of appropriate control drugs is important to compare and attribute any biological activity (in this case, multiple enzyme inhibition) with the compounds 5 a – 5 l . As a positive control, acarbose (for both α‐amylase and α‐glucosidase) was employed [40,41] …”
Section: Antioxidant Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…The usage of appropriate control drugs is important to compare and attribute any biological activity (in this case, multiple enzyme inhibition) with the compounds 5 a – 5 l . As a positive control, acarbose (for both α‐amylase and α‐glucosidase) was employed [40,41] …”
Section: Antioxidant Assaymentioning
confidence: 99%
“…The IC 50 values signify the concentrations of test samples that can 50 % inhibit the activity of an enzyme as compared to the control. [40,41] The In vitro studies revealed that compounds had effective α-glucosidase inhibitory potential than α-amylase enzyme. The In vitro α-glucosidase inhibitory studies revealed that 5 k had effective inhibitory potential than other samples tested.…”
Section: Inhibition Of α-Amylase and α-Glucosidasementioning
confidence: 99%
See 1 more Smart Citation
“…Different food products including milk, vegetables, and fruits have got anti-hyperlipidemic and anti-diabetic factors [ 14 ]. In the current scenario, the usage of phytochemical products for the treatment of anti-diabetic conditions has been trending, since they are associated with a low risk of developing adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the Artocarpus species are potentially used for both medicines as well as timber in the Asian subcontinent. The most popular of the species is Artocarpus heterophyllus (jackfruit) belongs to the Moraceae family and is a common household tree in India and Bangladesh [ 14 ]. Considering its economic value and abundance, several studies have been carried out on jackfruit suggesting that it possesses diverse medicinal uses including antioxidant, anti-inflammatory, antimicrobial, anticarcinogenic, antifungal, antineoplastic, and hypoglycemic effects inhibiting melanin biosynthesis and wound healing properties [ 15 ].…”
Section: Introductionmentioning
confidence: 99%